2016
DOI: 10.3389/fpsyg.2015.01969
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Music on Anxiety Induced by Fear of Heights in Virtual Reality

Abstract: Music is a potent mood regulator that can induce relaxation and reduce anxiety in different situations. While several studies demonstrate that certain types of music have a subjective anxiolytic effect, the reported results from physiological responses are less conclusive. Virtual reality allows us to study diverse scenarios of real life under strict experimental control while preserving high ecological validity. We aimed to study the modulating effect of music on the anxiety responses triggered by an immersiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 59 publications
1
34
1
Order By: Relevance
“…Finally, virtual reality allowed participants to perform actions that would be dangerous in the real world without the threat of any real danger. Despite no real danger, work by Meehan, Insko, Whitton, and Brooks [ 55 ] and Seinfeld et al [ 56 ] have found physiological measures of fear increased when viewing virtual heights, suggesting that participants react to heights in virtual environments as if they were real and that virtual environments are a reliable method for inducing emotional state. Thus, virtual reality serves as a great tool to manipulate the perception of danger without unnecessarily exposing participants to actual danger.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, virtual reality allowed participants to perform actions that would be dangerous in the real world without the threat of any real danger. Despite no real danger, work by Meehan, Insko, Whitton, and Brooks [ 55 ] and Seinfeld et al [ 56 ] have found physiological measures of fear increased when viewing virtual heights, suggesting that participants react to heights in virtual environments as if they were real and that virtual environments are a reliable method for inducing emotional state. Thus, virtual reality serves as a great tool to manipulate the perception of danger without unnecessarily exposing participants to actual danger.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the SSQ can analyze sickness in detail by classifying the questions. Items 1,6,7,8,9,15, and 16 indicate nausea; items 1, 2, 3, 4, 5, 9, and 11 indicate oculomotor sickness; and items 5,8,10,11,12,13, and 14 indicate disorientation sickness. In general, sickness is analyzed based on the sum of the weighted (nausea: 9.54, oculomotor: 7.58, disorientation: 13.92) detail items (nausea, oculomotor, and disorientation).…”
Section: Vr Sicknessmentioning
confidence: 99%
“…Sutherland [5] researched the first HMD system that provided 3D VR scenes for the visual sense. Since then, studies have been conducted to implement highly immersive VR by satisfying the various senses of users, including the auditory and tactile senses [6][7][8]. A wide variety of research on user-oriented interactions in VR has been conducted to this point, such as a study on capturing the elaborate motions of hands and fingers using optical markers and surface markers, and reflecting these motions in a virtual space [9,10], a study on the improvement of immersion by coupling the sense of touching the ground with a sound [11], and a study on the realistic expression of various behaviors such as going up stairs and pushing against a wall in a virtual space [12].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies looked at using music and diaphragmatic breathing to augment exposure therapy. In Seinfeld et al 43 , participants were immersed in VR scenarios that induced fear of heights while music played in the background. Anxiolytic effects were significant only after the experience but not during the experience.…”
Section: Others (N = 9)mentioning
confidence: 99%